Pesantren Based Madrasah Diniyah Education and the Realization of Quality Santri Outcomes - Nur Sahid; Dyah Nafidatus Shoimah (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Madrasah Diniyah Takmiliyah (MDT) Al-Badriyyah in Kediri City follows a distinctive approach to teaching kitab kuning (classical Islamic texts) as part of the broader Islamic scholarly tradition. Although its students come from a wide range of formal educational institutions and include both resident (mukim) and non-resident santri, the madrasah consistently produces graduates who meet the competency standards set by the Ministry of Religious Affairs. This study describes the planning, implementation, and educational outcomes of MDT Al-Badriyyah in Kediri City. A qualitative field-research approach was employed, with data collected through interviews, observation, and documentation, and analyzed through data collection, data reduction, data display, and conclusion drawing. The findings indicate that educational planning is grounded in the institution's vision and mission and in the values of thariqah al-ta'lim wa al-ta'allum (the path of seeking, practicing, and teaching knowledge), operationalized through a collaboratively developed curriculum. The learning process employs a combination of instructional methods bandongan, sorogan, memorization, syawir (scholarly discussion), lectures, and question-and-answer sessions supported by comprehensive assessment. The resulting educational outcomes are reflected in students' mastery of kitab kuning, their character development, and their practical application of Islamic knowledge in both social and religious life